Improvement of transport properties of Lix(Ni 0.8Co0.2)O2 oxide in the formation of Li x(Ni0.8Co0.2)O2/PANI composite - Mosqueda, Y.; Pérez-Cappe, E.; Rodriguez, G.; Varela, J. A.; Souza, E. (Wiley, 2005)
Several authors have proposed that lithium diffusivity is the restrictive step in the insertion and extraction lithium processes in Li 1-x[Ni(y-x)Nix]Co1-yO2 cathodic oxides. In this article we calculated the lithium diffusion coefficient and dc conductivity for Lix(Ni0.8Co0.2)O 2 and Lix(Ni0.8Co0.2)O 2/PANI composite by Galvanostatic Intermittent Titration Techniques (GITT) and Van der Pauw method, respectively. These materials were previously synthesized by novel chemical ways. Transport measurements indicated that the electronic and ionic transports are greater for composite than for the oxide. This effect was particularly evidenced by the better reversibility of Li-insertion in charge-discharge cycles in a lithium battery prototype for composite. © 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.